The Emerging Role of MicroRNAs in NAFLD: Highlight of MicroRNA-29a in Modulating Oxidative Stress, Inflammation, and Beyond - Hung-Yu Lin; Ya-Ling Yang; Pei-Wen Wang; Feng-Sheng Wang; Ying-Hsien Huang (Cells, 2020)
Non-alcoholic fatty liver disease (NAFLD) is a common cause of chronic liver disease and ranges from steatosis to steatohepatitis and to liver fibrosis. Lipotoxicity in hepatocytes, elevated oxidative stress and the activation of proinflammatory mediators of Kupffer cells, and fibrogenic pathways of activated hepatic stellate cells can contribute to the development of NAFLD. MicroRNAs (miRs) play a crucial role in the dysregulated metabolism and inflammatory signaling connected with NAFLD and its progression towards more severe stages. Of note, the protective effect of non-coding miR-29a on liver damage and its versatile action on epigenetic activity, mitochondrial homeostasis and immunomodulation may improve our perception of the pathogenesis of NAFLD. Herein, we review the biological functions of critical miRs in NAFLD, as well as highlight the emerging role of miR-29a in therapeutic application and the recent advances in molecular mechanisms underlying its liver protective effect.